The Puppy Who Wanted a Boy - Thayer, Jane, 1904-; McCue, Lisa (New York : Morrow, 1985)
When Petey the puppy decides that he wants a boy for Christmas, he discovers that he must go out and find one on his own.
Keywords: Dogs -- Fiction; Christmas -- Fiction; Children's book